Letter (copy) : Constantino Perez Bratos - Citrine, Walter, 1887-1983
012a-0089-001 Secretary's WMC/FEM/MT/864 PRIVATE. 3rd May, 1938. Mr. C. Dukes, National Union of General and Municipal Workers, 5, Endsleigh Gardens, LONDON, W.C.1. Dear Mr. Dukes, Constantino Perez Bratos. Referring to your letter of the 8th April, I received a letter on the 7th April from Lord Halifax saying that he would look into the question of the imprisonment of Senor Bratos at once. To-day, I have received a further letter from him in which he says that they have passed on the information which I sent to their Agent at Burgos for such action as he may be able to take on Senor Bratos' behalf. He says that he will not fail to keep me informed of any developments. I have replied to Lord Halifax and as soon as we hear anything further, we shall let you know. Yours sincerely, General Secretary. 292/946/12a/89